Studi Pengemasan terhadap Umur Simpan dan Kesegaran Gonda (Sphenoclea zeylanica Gaertn) - JAYA, I MADE PRANA; SUKEWIJAYA, I MADE; GUNADI, I GUSTI ALIT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.5, No.2, April 2016, 2016)
The Study of Packaging Shelf Life and Freshness of Gonda (Sphenoclea zeylanica Gaertn) The aim of this study is to determine the treatment of packaging which able to maintain shelf life and freshness of Gonda longer . This research was conducted at the Laboratory of Ecophysiology Faculty of Agriculture, University of Udayana. The method used was a completely randomized design (CRD) using any combination of two factors and repeated 4 times. Each treatment packaging using 5 sticks Gonda. Attempted treatment is the presence of root and gonda packaging materials. The result of the analysis, showed the influence of the presence of roots only significant to the variable defective products and product defects and product freshness in the first day after the harvest. Packaging treatment effect not only significant to the variable weight loss. The interaction between the presence of roots with packaging shown only two variables significantly affected, that chlorophyll in leaves 1 day after harvest and product defect and product freshness 1 day after harvest. Plastic packaging is packaging which ability to maintain shelf life and freshness gonda better than controls, packaging with banana leaves and paper. Gonda treatment rooted in plastic packaging (A1P2) capable of maintaining shelf life of gonda to be used as a vagetable maximum of 2,50 days. Furthermore, gonda treatment without roots and without packaging (A0P0) and gonda rooted without packaging (A1P0) for 1 day, gonda without roots with banana leaf packaging (A0P1) and gonda roots with banana leaf packaging (A1P1) for 2 days, gonda treatment without roots in plastic packaging (A0P2) for 2,5 days and gonda treatment without roots with newspaper packaging (A0P3) and gonda with roots wih newspaper packaging (A1P3) for 1,5 days.
Keywords: Gonda; Sphenoclea zeylanica Gaertn; Postharvest; packaging